2017
DOI: 10.3389/fmicb.2017.00691
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles in Cell Lines Infected with Classical Swine Fever Virus

Abstract: Viruses require energy and biosynthetic precursors from host cells for replication. An understanding of the metabolic interplay between classical swine fever virus (CSFV) and host cells is important for exploring the complex pathological mechanisms of classical swine fever (CSF). In the current study, and for the first time, we utilized an approach involving gas chromatography coupled with mass spectrometry (GC-MS) to examine the metabolic profiles within PK-15 and 3D4/2 cells infected with CSFV. The different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Our previous work has confirmed that CSFV rebuild cellular metabolic programs in vitro , thus aiding viral replication (Hongchao et al, 2017; Wenjie et al, 2017). However, systematic changes in lipid metabolites in CSFV-infected cells remain unknown.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our previous work has confirmed that CSFV rebuild cellular metabolic programs in vitro , thus aiding viral replication (Hongchao et al, 2017; Wenjie et al, 2017). However, systematic changes in lipid metabolites in CSFV-infected cells remain unknown.…”
Section: Introductionsupporting
confidence: 55%
“…It is well-known that viruses alter host metabolism, especially lipid metabolism, to facilitate their infection and replication (Heaton and Randall, 2011). Like other members of the Flaviviridae family, CSFV can also cause cellular metabolic disorders and lead to a series of pathological reactions, such as high fever, multiple hemorrhage, leukopenia and inflammation (Kleiboeker, 2002; Lohse et al, 2012; Hongchao et al, 2017). In the current study, we provided for the first time observations on the lipids changes in the serum of CSFV-infected piglets based on UHPLC-QTOF-MS, which might provide suitable targets for drug intervention and therapeutic vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, lactate participates in mitochondrial oxidative activity in cultured CHO cells and that LDHB localizes to the mitochondria [25,26]. We and other researchers have found that CSFV infection promoted lactate release and inhibits pyruvate release [38,39]. Based on these results, we hypothesized that LDHB may also elicit an effect on mitophagy.…”
Section: Introductionmentioning
confidence: 77%
“…The quality of the models is described by the R 2 X or R 2 Y and Q 2 values. Differential metabolites were determined by the combination of variable importance in the projection (VIP) value (>1) of the OPLS-DA model and the p -values (<0.05) from two-tailed student's t -tests on normalized peak intensities (31).…”
Section: Methodsmentioning
confidence: 99%